Effect Of Cadmium Element On The Ecological Status Of Irrigated Soils In Nishan District (Journal of Pedagogical Inventions and Practices, 2022)
The article presents data on the accumulation, excess of the maximum permissible concentration of cadmium in irrigated sierozem-meadow, desert-sandy, as well as gray-brownmeadow soils of the Nishan district of the Kashkadarya region